Schumpeter in a matrix: a Stock Flow Consistent analysis of technological change - Alessandro Caiani; Antoine Godin; Stefano Lucarelli (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
Schumpeter showed that the boom and bust cycles are intrinsically related to the functioning of the capitalist economy. These boom and bust cycles are inherent to the rise innovation. Our paper analyses innovation cycles in a stock flow consistent framework. It focuses on the essential role of internal and external finance in the emergence of a new technological paradigm. We present two models. The first one, as a tribute to Schumpeters work, follows strictly Schumpeters description of the business cycles induced by technological change, except for the financial side. The second model presents a multi-sectorial economy composed of consumption and capital goods industries, a banking sector and two households sectors: capitalists and wage earners. The stock flow consistent approach allows us to track the flows of funds resulting from the rise of innovators in the system. The dynamics of prices, employment and wealth distribution among the different sectors is analysed. Above all, the role of financial-innovation nexus is underlined. The paper builds the grounds for a wider analysis of schumpeterian structural changes described in Schumpeter (1934/1912) and Schumpeter (1964/1939) We find this particularly relevant to understand the impact and potential sources of instability of an ever more financialized monetary economy of production.
Keywords: O30; O4; E32; 330; Schumpeter; Innovation; Stock Flow Consistent Models; Monetary Circuit